2016
DOI: 10.1115/1.4032934
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Transport and Deposition Efficiency of Oblate and Prolate Nano- and Micro-particles in a Virtual Model of the Human Airway

Abstract: A model for the motion and deposition of oblate and prolate spheroids in the nano-and microscale was developed. The aim was to mimic the environment of the human lung, but the model is general and can be applied for different flows and geometries for small nonspherical particle Stokes and Reynolds numbers. A study of the motion and orientation of a single oblate and prolate particle has been done yielding that Brownian motion disturbs the Jeffery orbits for small particles. Prolate microparticles still display… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Solid round particles with a density of 1200 kg/m 3 were utilized with an injection rate of 1.3 g/mm 3 /s for all particles throughout the inhalation process. Other studies have demonstrated the importance of modeling the Brownian motion [37,38] for nanoparticles. However, the present investigation does not include modeling of the Brownian motion due to the dominance of the flow inertial on micron particle depositions in large and medium airways.…”
Section: Computational Models Of Particle Transport Andmentioning
confidence: 99%
“…Solid round particles with a density of 1200 kg/m 3 were utilized with an injection rate of 1.3 g/mm 3 /s for all particles throughout the inhalation process. Other studies have demonstrated the importance of modeling the Brownian motion [37,38] for nanoparticles. However, the present investigation does not include modeling of the Brownian motion due to the dominance of the flow inertial on micron particle depositions in large and medium airways.…”
Section: Computational Models Of Particle Transport Andmentioning
confidence: 99%
“…For example, even small deviations from a perfect axisymmetric rod shape can lead to the appearance of doubly periodic and chaotic orbits, and these have been studied both theoretically and experimentally [8][9][10] . The proximity of channel walls [11][12][13][14][15] , inertia 6 and the viscoelasticity of the shearing fluid 16 have also been shown to perturb the Jeffery solution. Furthermore, noise may also affect the orbits: for smaller rods, where Brownian motion (i.e.…”
mentioning
confidence: 99%
“…The Stokes diameters for a prolate spheroid are given by and the ones for oblate spheroids are given by Holmstedt et al. 43 …”
Section: Simulation Set-upmentioning
confidence: 99%